2021
DOI: 10.1101/2021.06.28.21259529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of natural selection on global patterns of genetic variation, and association with clinical phenotypes, at genes involved in SARS-CoV-2 infection

Abstract: The COVID-19 pandemic caused by SARS-COV-2 has had a devastating impact on population health. We investigated global patterns of genetic variation and signatures of natural selection at host genes relevant to SARS-CoV-2 infection (ACE2, TMPRSS2, DPP4, and LY6E). We analyzed novel data from 2,012 ethnically diverse Africans, 15,997 individuals of European (7,061) and African (8,916) ancestry recruited by the Penn Medicine BioBank (PMBB), and comparative data from 2,504 individuals from the 1000 Genomes project.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Neutralizing antibodies to the S protein provide near-complete protection against rechallenge in animal studies 35 . Recent modelling studies have suggested that neutralizing antibodies are highly predictive of protection against infection or severe disease 36 , with a second modelling study suggesting a tight correlation between neutralizing antibody levels and reported efficacy across several COVID-19 vaccine trials 18 , and a third study derived from efficacy trials indicating that both binding and neutralizing antibody titres correlate with protection 37 .…”
Section: Correlates Of Protectionmentioning
confidence: 99%
“…Neutralizing antibodies to the S protein provide near-complete protection against rechallenge in animal studies 35 . Recent modelling studies have suggested that neutralizing antibodies are highly predictive of protection against infection or severe disease 36 , with a second modelling study suggesting a tight correlation between neutralizing antibody levels and reported efficacy across several COVID-19 vaccine trials 18 , and a third study derived from efficacy trials indicating that both binding and neutralizing antibody titres correlate with protection 37 .…”
Section: Correlates Of Protectionmentioning
confidence: 99%
“…Epithelial cells of the oral cavity, nasal duct, and upper airway are the primary targets for SARS-CoV-2 [ 1 , 2 , 3 ], by the interaction of the viral spike protein (S-protein) with the human angiotensin converting enzyme 2 (ACE2) and other host proteins and glycosaminoglycans [ 4 , 5 ]. Moreover, a recent study defined the susceptibility to SARS-CoV-2 infection as the result of a combination between the genetic variations of SARS-CoV-2 and the genetics of the host [ 6 ]. This implies that the different genetic variants of the viral S-protein bind with different strength to ACE2 variants, and this might play a role in the severity of infection.…”
Section: Introductionmentioning
confidence: 99%